Self-Control or Crime Control: Teachers' Insights on Good Practices in 1:1 Classrooms and Implications for Professional Development - Synnøve H. Amdam; Ilka Nagel; Morten B. Njå; Sanna Forsström (MDPI AG, 2024)
Norway ranks high in digitalization in schools, with over 90% of students in grades 1-10 having their own digital device supplied by their school districts and reporting the highest use of digital tools globally in the latest PISA report. However, research shows that implementation processes and competence measures for teachers' professional use of digital devices vary considerably between schools. This study aims to inform the development of research-practice partnership (RPP) measures focused on professional digital competence development in digitalizing schools internationally by exploring what teachers consider important for good teaching practices in 1:1 computing classrooms. We draw on both closed and open survey responses from 1505 Norwegian teachers in highly digitalized schools where the most experienced teachers have had 1:1 computing since 2014. The findings show that classroom management is seen as gradually more important with higher digital teaching competence and more experience, but that the teachers' understandings of what digital competence entails and their use of classroom management strategies are rather limited. The study concludes that professional competence development measures that provide broader understandings of digital competence and classroom management are needed, dependent on competence levels and experience, as well as systematic training of students' digital self-regulation.